2022
DOI: 10.1097/mpg.0000000000003483
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gastroesophageal Reflux Disease in Esophageal Atresia Patients: A Cross-Sectional Survey amongst International Clinicians

Abstract: Objectives: After surgical repair, up to 70% of esophageal atresia (EA) patients suffer from gastroesophageal reflux disease (GERD). The ESPGHAN/NASPGHAN guidelines on management of gastrointestinal complications in EA patients were published in 2016. Yet, the implementation of recommendations on GERD management remains poor. We aimed to assess GERD management in EA patients in more detail, to identify management inconsistencies, gaps in current knowledge, and future directions for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…35 Moreover, studies found significant variation in the implementation of the guidelines, possibly due to lack of awareness thereof and/or the lack of strong evidence underlying the recommendations. 36,37 Hence, the routine use of PPIs for the first year of life as recommended by the current guidelines may need to be revisited. 3 Symptoms in the EA cohort are often nonspecific and do not help to distinguish between GERD, EoE, dysmotility, and stricture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Moreover, studies found significant variation in the implementation of the guidelines, possibly due to lack of awareness thereof and/or the lack of strong evidence underlying the recommendations. 36,37 Hence, the routine use of PPIs for the first year of life as recommended by the current guidelines may need to be revisited. 3 Symptoms in the EA cohort are often nonspecific and do not help to distinguish between GERD, EoE, dysmotility, and stricture.…”
Section: Discussionmentioning
confidence: 99%
“…No association was also found between the duration of postoperative acid suppression and anastomotic stricture development 35 . Moreover, studies found significant variation in the implementation of the guidelines, possibly due to lack of awareness thereof and/or the lack of strong evidence underlying the recommendations 36,37 . Hence, the routine use of PPIs for the first year of life as recommended by the current guidelines may need to be revisited 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The choice of diagnostic approach should be guided by the patient’s specific symptoms, medical history, and clinical presentation. A multidisciplinary approach involving gastroenterologists, radiologists, and other specialists is often necessary for optimal diagnostic accuracy and management of GERD [ 10 , 50 ]. Further research and advancements in diagnostic techniques are warranted to enhance diagnostic precision and improve patient outcomes in GERD: upper endoscopy, ambulatory acid (pH) probe test [ 39 ], X-ray of the upper digestive system [ 51 ], esophageal manometry [ 51 ], and transnasal esophagoscopy [ 52 ].…”
Section: Gastroesophageal Reflux Disease (Gerd)mentioning
confidence: 99%
“…Morever, indications and duration of PPIs therapy varied widely among centers as demonstrated by a recent survey on the GERD management of EA patients. 6 Herein, we aimed to gather and review the results of available clinical studies, to evaluate evidence in the use of PPIs in pediatric patients with EA, with a special focus on benefits and risks during the first years of life.…”
Section: Introductionmentioning
confidence: 99%
“…As evidence of benefits are weak, long‐term use of PPIs raises safety concerns. Morever, indications and duration of PPIs therapy varied widely among centers as demonstrated by a recent survey on the GERD management of EA patients 6 …”
Section: Introductionmentioning
confidence: 99%